Design and synthesis of zinc protoporphyrin IX-adamantane/cyclodextrin/cellulose nanocrystals complexes for anticancer photodynamic therapy. (1st June 2021) - Ndong Ntoutoume, Gautier M.A.; Granet, Robert; Mbakidi, Jean-Pierre; Constantin, Eléna; Bretin, Ludovic; Léger, David Y.; Liagre, Bertrand; Chaleix, Vincent; Brégier, Frédérique; Sol, Vincent
Graphical abstract: Abstract: Two protoporphyrin IX (PpIX) adamantane derivatives were synthesized and then metallated with zinc. The Zn-PpIX derivatives, exhibiting a high singlet oxygen quantum yield, were tested for their photodynamic activity against the HT-29 cell line. In order to enhance their water-solubility and their cellular bioavailability, these photosensitizers were encapsulated into the hydrophobic cavity of cyclodextrins (CD) previously attached to cellulose nanocrystals (CNCs) via electrostatic interactions. Under illumination, the encapsulated adamantanyl-porphyrins exerted an enhanced in vitro cytotoxicity, as compared with the corresponding free photosensitizers.